Evaluating The Human Rights Committee's Advancement of Norms to Protect Individuals of Diverse Sexual Orientation, Gender Identity and Expression and Sex Characteristics - Stærfeldt, Leonora Kleppa (Department of Public Law, 2022)
Throughout the world human rights abuses are committed against individuals on the grounds of their sexual orientation, gender identity and expression or sex characteristics (SOGIESC). The Human Rights Committee (HRC), which is the monitoring body of the International Covenant on Civil and Political Rights (ICCPR), can play a role in ensuring that human rights violations targeting SOGIESC diverse groups end. This can be done through the advancement of SOGIESC norms. By advancing SOGIESC norms the HRC would affirm that the rights in the ICCPR extend to SOGIESC diverse groups, thus promoting protection of SOGIESC diverse groups' civil and political rights. This dissertation examines the extent to which the HRC advances SOGIESC norms. This is realized through a combination of quantitative and qualitative analysis of how the HRC has engaged with SOGIESC under the auspice of its three monitoring functions – Views in individual communications, Concluding Observations and General Comments. The findings are explored within the theoretical framework of norm formation and theories about intrinsic qualities of successful norms. The analysis reveals that the HRC's advancement of SOGIESC norms is characterized by uneven progress. On one hand, the analysis demonstrates that the HRC has progressed significantly in its advancement of SOGIESC norms during the last 25 years. The HRC has increasingly advanced norms to affirm that numerous rights enshrined in the ICCPR extend to SOGIESC diverse groups. On the other hand, the analysis shows that progression on advancement of SOGIESC norms by the HRC is qualified. The HRC has not advanced the distinct SOGIESC norms equally, nor do the SOGIESC norms advanced by the HRC apply equally to individuals of diverse sexual orientation and gender identity and expression and sex characteristics. It is concluded that there is still scope for the HRC to improve advancement of SOGIESC norms. The dissertation offers three recommendations as to how the HRC can improve advancement of SOGIESC norms to achieve more comprehensive protection of SOGIESC diverse groups' human rights.